(untitled) (مجلة المنصور, 2023)
This study is devoted for searching free e-books problem because of its importance with spreading the e-libraries. When the web client asking for a free e-books the search engine returns selling e-books sites, this produce a conclusion of inaccuracy about this search engine. According to this case this study suggest the philosophy of clustering a sample of web sites on the number of links which lead to the downloadable e-books and rank this sites higher than the others with matching the entered keywords. Three clusters have been noticed (sites with high rank, sites with medium ranking, and low ranked sites). The proposed system (Ico.com) has been built form many components; the first is the web crawler which is a software Program for fetching data of web pages (like page address, subject, number of links…etc), the second component is the clustering program written using (VB6.0) language to cluster the web pages databases according to the number of links to real existing downloadable books, and the last component is the search engine interface which is built using HTML and VB script under Active server pages technology. This work reached to increasing the search engine accuracy using factors like analyzing the number and the type of links by mining the web site’s database to improve accuracy for search engines.